Emergent issues in the field of drug abuse - Levy, Judith A.; Stephens, Richard C.; McBride, Duane C. (Stamford, Conn. : JAI, 1999)
This is the eighth volume in a series dedicated to publishing current research and conceptual papers in the broad-ranging area of the sociology of health.
Future directions in research, intervention, and prevention in the field of drug abuse / Richard C. Stephens, Duane C. McBride, Judith A. Levy -- Epidemiology and prevention research among U.S. children and adolescents / Zili Sloboda -- Adolescent substance use and adult health status / Ryan E. Spohn, Howard B. Kaplan -- Depression, drug use, and health services need, utilization, and cost / Duane C. McBride, Holly Van Buren, Yvonne M. Terry, Burton J. Goldstein -- The motivation-readiness factor in drug treatment implications for research and policy / George De Leon, Gerald Melnick, Josephine Hawke -- The impact of centralized intake on access to treatment and satisfaction with intake procedures / Christy K. Scott, Randolph D. Muck, Mark A. Foss -- Health services for chronic drug users in an era of managed care / Clyde B. McCoy, Lisa R. Metsch, Dale D. Chitwood, James E. Rivers, H. Virginia McCoy, Sarah Messiah -- Moral belief and drug problem recognition in three ethnic groups / Douglas Longshore, Kathy Sanders-Phillips -- The trajectory of recovery among drug-dependent Puerto Rican mothers / Timothy Black, Monica Hardesty -- Models of adaptation to termination of the SSI/SSDI addiction disability / Paul J. Goldstein, Tammy L. Anderson, Igor Schyb, James Swartz -- The impact of the NIDA Cooperative Agreement programs on HIV risk among crack and injection drug users / Richard C. Stephens, Carol F. Kwiatkowski, Robert E. Booth -- New directions in HIV prevention among drug users settings, norms, and network approaches to AIDS prevention (SNNAAP): A social influence approach / Carl A. Latkin, Amy R. Knowlton -- The role of employment cycles and incentives in the recruitment of drug users / Grace L. Reynolds, Dennis G. Fisher, Henry H. Cagle, Mark E. Johnson -- Community organization and drug prevention readiness / Mark Peyrot, H. Lovell Smith -- The transformation of private alcohol problem treatment / Paul M. Roman, J. Aaron Johnson, Terry C. Blum -- From research to practice / Barry S. Brown.
Includes bibliographical references.
Description based on print version record.
Keywords: Drug abuse; Drug abuse -- Social aspects; Drug abuse -- Treatment; Public health & preventative medicine; Health systems & services; Social Science -- General